KEGIATAN PESTA SIAGA UNTUK MENGEMBANGKAN KARAKTER JUJUR DAN GOTONG ROYONG SISWA SDN BETRO SEDATI SIDOARJO - Lestari, Bernadetta Budi; Suhartono, Suhartono (Universitas PGRI Semarang, 2021)
Background of the study in this research is studentâ€™s charcter in modern era getting worst. It has taken information from public media that shown the most diverge of studentâ€™s attitude. Furthermore , theÂ teachers try to develop character education using intracurricular and extracurricular. Scout is theÂ extracurricular that used to develop studentâ€™s chracter, one of the activities is â€œpesta siagaâ€. Statements of the problem in this research are (1) how is the implementation education of characterÂ in Betro Sedati Sidoarjo Elementary school? (2) how is the implementation â€œpesta siagaâ€ to the scout extracurricular in Betro Sedati Sidoarjo Elementary school? (3)Â how are develop and increasing the student honesty and mutual cooperation characters for implementation of â€œpesta siagaâ€ in Betro Sedati Sidoarjo Elementary school? In this research using qualitative research method. The source data are 60 students from boy and girl scout. The dataÂ will calculating with percentage formula than described.The result of the study are (1) implementation education of character in Betro Sedati Sidoarjo Elementary school is very great from the past until now. (2) implementation of â€œpesta siagaâ€ to the scout extracurricular in Betro Sedati Sidoarjo Elementary school running well as standard operational procedure. (3) from the implementation of â€œpesta siagaâ€ had found honesty chracter that increasing which are student had tell the truth or being honest and doing mutual coorperation that make this research have done can categorize that verry better.